Reverse and Green Logistics Implementation for Sewage Treatment Plant Installation of “BELLA” Apartment Building - Rivaldy, M. Labib; Dian Sua Pratama, Bayu (Riviera Publishing, 2023)
Industrial and household operations mostly produce liquid waste that can harm the environment without further processing or processing.